PERANCANGAN USER INTERFACE APLIKASI RUMAH SEHAT RETNO BERBASIS SMARTPHONE DAN EVALUASI SYSTEM USABILITY SCALE (SUS) - Pradea Wulandari (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Almost everyone demands more efficient public services, one of which is health services. One of the clinics in Bulukumba district is a clinic that is visited by many people. Many people come to seek treatment at the clinic because the clinic has been trusted by many local residents, because many residents come to the clinic which eventually causes queues. From these problems, this study aims to design a smartphone-based online registration system for outpatients in one of the clinics in Bulukumba district to provide queuing information and an estimated time when the patient will be served. In this study, the questionnaire used SUS. The research flow used was the UI design design for the Retno Healthy Home application, in this study the application used to create a prototype was a web-based figma application and also used a web-based draw.io application to create diagrams and sketch the initial design in black and white. In this study, 27 respondents used random sampling technique. In the evaluation results of UI design using the SUS questionnaire, it gets an average value of 68.